Special composite additive for low-ash capacitor film polypropylene
By providing a special compound additive for polypropylene with low ash content for capacitor films, the problem of high ash content in existing BOPP electrical films is solved, improving material performance and meeting user needs.
Patent Information
- Application Number
- CN202411469035.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
The existing BOPP electrical film has a high ash content, which affects its electrical and mechanical properties. It lacks standards for capacitor film polypropylene, making it difficult to meet users' needs for high-purity materials.
Provide a special compound additive for low-ash capacitor film polypropylene, including the ratio of F401, compound antioxidant and nucleating agent. By optimizing the formula and process flow, the ash content is reduced and the mechanical, optical and thermodynamic properties of the material are improved.
It significantly reduces the ash content of the capacitor film, improves its mechanical properties, optical properties and thermodynamic properties, and meets the user's demand for high-purity materials.
Smart Images

Figure BDA0005094204660000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of capacitor films, and in particular to a special composite auxiliary agent for low-ash capacitor film polypropylene. Background Art
[0002] Capacitors are one of the indispensable electronic components for electronic information, household appliances, and the power industry, and BOPP capacitor film is the main raw material. Polypropylene (PP) electrical film is a high-frequency dielectric insulating material with excellent electrical properties and is the top product of BOPP film. BOPP capacitor film is the main dielectric material of film capacitors, accounting for about 70% of the production cost of film capacitors. The quality of capacitor film directly affects the performance indicators of capacitors such as stable capacity, excellent withstand voltage, insulation resistance performance, safety of use, and life cycle. The acquisition rate of finished products produced by capacitor film is low, the quality control requirements are high, and the process technology is very difficult, which is a high value-added product. Among the national standards, industry standards, and local standards, there are only relevant standards for polypropylene film for capacitors, and no standards for polypropylene resin. Through market research, it is learned that downstream users require high purity for the special materials of BOPP electrical film, and the ash content must be less than 50ppm, preferably below 30ppm, to ensure the film's good breakdown voltage, volume resistance, dielectric constant, dielectric loss and other electrical properties, and the mechanical properties, optical properties, and thermodynamic properties of capacitor film polypropylene are insufficient, so it is necessary to make improvements. Summary of the invention
[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a special composite additive for low-ash capacitor film polypropylene to solve the above problems.
[0004] The object of the present invention is achieved by: a special composite additive for low-ash capacitor film polypropylene, comprising the following components in the following proportions:
[0005] F401 99.4-99.6%
[0006] Compound antioxidant 0.4%
[0007] Nucleating agent 0-0.2%.
[0008] Preferably, the composition ratio of F401 is 99.4-99.5%, and the type of nucleating agent is TMB-5, and the composition ratio is 0.1-0.2%.
[0009] Preferably, the composition ratio of F401 is 99.4-99.5%, and the type of nucleating agent is CH-6N, and the composition ratio is 0.1-0.2%.
[0010] Preferably, the composition ratio of F401 is 99.4%, and the type of nucleating agent is HPN-715, and the composition ratio is 0.1-0.2%.
[0011] Preferably, the composition ratio of F401 is 99.4-99.5%, and the type of nucleating agent is TMP-7, and the composition ratio is 0.1-0.2%.
[0012] Preferably, the composition ratio of F401 is 99.4%, and the type of nucleating agent is TMP-5+CH-6N, wherein the composition ratio of TMP-5 and CH-6 is 0.1% each.
[0013] Preferably, the composition ratio of F401 is 99.4%, and the type of nucleating agent is TMP-5+HPN-715, wherein the composition ratio of TMP-5 and HPN-715 is 0.1% respectively.
[0014] The present invention has the following beneficial effects:
[0015] The low-ash capacitor film polypropylene special composite additive comprises the following components in the following proportions: F40199.4-99.6%, composite antioxidant 0.4%, nucleating agent 0-0.2%, the composite antioxidant is a high-phosphorus phosphite antioxidant SONOX626 and an inorganic acid absorbent hydrotalcite, and through reasonable formula improvement, the mechanical properties, optical properties and thermodynamic properties of the capacitor film polypropylene are improved and optimized, and the composite antioxidant is worthy of popularization and application.
[0016] In terms of reducing ash content, the impurities brought into the raw material propylene have a significant impact on the ash content of the product. The trace amount of harmful substances (such as H2O, CO, CO2, O2, S, alkynes, dienes, etc.) contained in the impurities affect the activity and directional ability of the catalyst. In order to ensure the normal progress of the reaction, it is necessary to increase the amount of triethyl aluminum to eliminate the influence of impurities. On the basis of meeting the activator dosage required for production, the activator injection amount should be reduced as much as possible. On the basis of ensuring the high quality of the raw materials, the activator injection amount is low and cannot form enough active centers with the catalyst, which will lead to weak polymerization reaction, low single-pot output, and high ash content of the final product output; with the increase of the activator injection amount, the reaction situation will gradually improve, the single-pot output will gradually increase, and the product ash content will gradually decrease; however, when the activator injection amount increases to a certain extent, the activator is surplus, and this part of the activator will not optimize the reaction strength and single-pot output, and will eventually increase the product ash content in the form of residue. Therefore, a suitable aluminum-titanium ratio is one of the important means to ensure low ash content in the product.
[0017] External electron donors play a role in improving the isotactic index of polypropylene in the polymerization reaction. When the isotactic index is too low, it is easy to cause sticking of materials, adhesion to the inner wall of the reactor or clogging of the pipeline, resulting in passive production. Therefore, the role of external electron donors cannot be ignored. On the premise of meeting the requirements of the product isotactic index, try to reduce the amount of external electron donors. External electron donors mainly improve the activity and directional ability of active species by selectively complexing the non-isotactic polypropylene active center. Too much addition will complex with the isotactic active center, reducing the activity of the catalyst. Therefore, on the basis of meeting the requirements of the product isotactic index, try to reduce the amount of external electron donors.
[0018] At the same time, in terms of the environment, during the granulation and packaging process, the product will be exposed to the external environment. When there is a lot of dust in the external environment, the ash content of the product will increase significantly. Therefore, try to control the on-site environment to ensure that the granulation and packaging processes are carried out in a closed, dust-free space.
[0019] A filling funnel is added to the polymerization kettle to form a one-to-one correspondence between the catalyst, activator and external electron donor. The filling method is: 1) First add the activator, use the strong reducing property of the activator to create a good environment for the catalyst, and then add the catalyst; 2) After the activator is added, stir for 10 to 20 minutes to ensure the activator's impurity removal effect before adding the catalyst; 3) Under the premise of ensuring that all the catalyst is added to the reactor, try to reduce the amount of propylene used to wash the catalyst.
[0020] At the same time, due to the rust in the reaction polymerization kettle and the connected pipelines, the ash content of the product will also increase. Therefore, in the start-up phase, the system must be replaced and purged to ensure that the impurity content in the system is minimized. If necessary, stainless steel materials can be used instead of carbon steel materials. DETAILED DESCRIPTION
[0021] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the technical scheme in the specific implementation mode of the present invention is clearly and completely described below to further illustrate the present invention. Obviously, the specific implementation mode described is only a part of the implementation mode of the present invention, rather than all styles.
[0022] The present invention is described in further detail below.
[0023] Embodiment 1:
[0024] A composite additive specially used for low-ash capacitor film polypropylene, comprising the following components in the following proportions:
[0025] F401 99.4-99.6%
[0026] Compound antioxidant 0.4%
[0027] Nucleating agent 0-0.2%
[0028] The composite antioxidants commonly used in the prior art are generally antioxidants SONOX168 and calcium stearate. Antioxidant SONOX168 is a phosphite antioxidant with excellent performance, which has strong anti-extraction properties, is stable to hydrolysis, and can significantly improve the light stability of the product. It can be used in combination with a variety of phenolic antioxidants. In this embodiment, a high-phosphorus phosphite antioxidant SONOX626 and an inorganic acid absorber hydrotalcite are used to replace the antioxidant SONOX168 and calcium stearate in the original auxiliary agent system, respectively, and the melt index stability of polypropylene is significantly improved.
[0029] In terms of yellow index performance, the yellow index can characterize the color depth of polypropylene. Generally, the lower the yellow index, the better the appearance and color of the polypropylene product. The yellow index of the antioxidant SONOX626 and inorganic acid absorber hydrotalcite formula is also significantly better than the antioxidant SONOX168 and calcium stearate formula, in which the melt flow rate of polypropylene particles is reduced by 1.57. Therefore, the formula containing the antioxidant SONOX626 and hydrotalcite system can significantly improve the appearance of polypropylene thin-wall injection molding.
[0030] The oxidation induction period is a method that uses differential thermal analysis to test the degree of accelerated aging of plastics in high-temperature oxygen based on the exothermic reaction when the plastic molecular chain breaks. It is used to evaluate the anti-aging performance of plastics. This experiment tested the oxidation induction period of the second extruded polypropylene particles at 190°C, and the oxidation induction periods of the above two groups of formulas were basically the same. The oxidation induction period index is mainly related to the free radical terminator. In this experiment, the hindered phenol main antioxidant SONOX1010 can terminate alkoxy free radicals, and the amount of antioxidant SONOX1010 added in the two groups of formulas is the same, so the oxidation induction period of each group is basically the same. In order to verify the effect of the formula of phosphite antioxidant SONOX626 and inorganic acid absorber hydrotalcite, five extrusions were carried out, and samples were retained after each extrusion to test the melt flow rate and yellow index. Finally, the experiment showed that the melt flow rate stability and yellow index stability of the antioxidant SONOX626 and inorganic acid absorber hydrotalcite formula after multiple processing were better than those of the antioxidant SONOX168 and calcium stearate formula, that is, the high-phosphorus phosphite antioxidant SONOX626 and inorganic acid absorber hydrotalcite were used to replace the antioxidant SONOX168 and calcium stearate in the original additive system, and the processing stability of polypropylene was significantly improved.
[0031] In terms of mechanical properties, the bending modulus of polypropylene is slightly improved after adding hydrotalcite. This is mainly because hydrotalcite is an inorganic powder material with a smaller particle size, with a particle size of 0.2-1.0 μm. During the cooling process of the polypropylene melt, the fine inorganic talc powder has a certain heterogeneous nucleation effect, which can promote the crystallization of polypropylene, thereby improving the mechanical properties of the material.
[0032] In summary, it can be concluded that the formulation containing antioxidant SONOX626 and hydrotalcite system can significantly improve the yellowness index and the appearance of polypropylene thin-wall injection molding compound compared with the formulation containing antioxidant SONOX168 and calcium stearate. In addition, in polypropylene thin-wall injection molding compound, inorganic acid absorber hydrotalcite has a certain synergistic effect with nucleating agent, which can promote the crystallization of polypropylene and improve the corresponding mechanical properties.
[0033] In terms of reducing ash content, the impurities brought into the raw material propylene have a significant impact on the ash content of the product. The trace amount of harmful substances (such as H2O, CO, CO2, O2, S, alkynes, dienes, etc.) contained in the impurities affect the activity and directional ability of the catalyst. In order to ensure the normal progress of the reaction, it is necessary to increase the amount of triethyl aluminum to eliminate the influence of impurities. On the basis of meeting the activator dosage required for production, the activator injection amount should be reduced as much as possible. On the basis of ensuring the high quality of the raw materials, the activator injection amount is low and cannot form enough active centers with the catalyst, which will lead to weak polymerization reaction, low single-pot output, and high ash content of the final product output; with the increase of the activator injection amount, the reaction situation will gradually improve, the single-pot output will gradually increase, and the product ash content will gradually decrease; however, when the activator injection amount increases to a certain extent, the activator is surplus, and this part of the activator will not optimize the reaction strength and single-pot output, and will eventually increase the product ash content in the form of residue. Therefore, a suitable aluminum-titanium ratio is one of the important means to ensure low ash content in the product.
[0034] External electron donors play a role in improving the isotactic index of polypropylene in the polymerization reaction. When the isotactic index is too low, it is easy to cause sticking of materials, adhesion to the inner wall of the reactor or clogging of the pipeline, resulting in passive production. Therefore, the role of external electron donors cannot be ignored. On the premise of meeting the requirements of the product isotactic index, try to reduce the amount of external electron donors. External electron donors mainly improve the activity and directional ability of active species by selectively complexing the non-isotactic polypropylene active center. Too much addition will complex with the isotactic active center, reducing the activity of the catalyst. Therefore, on the basis of meeting the requirements of the product isotactic index, try to reduce the amount of external electron donors.
[0035] At the same time, in terms of the environment, during the granulation and packaging process, the product will be exposed to the external environment. When there is a lot of dust in the external environment, the ash content of the product will increase significantly. Therefore, try to control the on-site environment to ensure that the granulation and packaging processes are carried out in a closed, dust-free space.
[0036] A filling funnel is added to the polymerization kettle to form a one-to-one correspondence between the catalyst, activator and external electron donor. The filling method is: 1) First add the activator, use the strong reducing property of the activator to create a good environment for the catalyst, and then add the catalyst; 2) After the activator is added, stir for 10 to 20 minutes to ensure the activator's impurity removal effect before adding the catalyst; 3) Under the premise of ensuring that all the catalyst is added to the reactor, try to reduce the amount of propylene used to wash the catalyst.
[0037] At the same time, due to the rust in the reaction polymerization kettle and the connected pipelines, the ash content of the product will also increase. Therefore, generally in the start-up phase, the system must be replaced and purged to ensure that the impurity content in the system is minimized. If necessary, stainless steel materials can be used instead of carbon steel materials.
[0038] In summary, the raw materials were mixed according to the formula in Table 1 below, and the raw materials were mixed at high speed for 3 minutes with a high-speed mixer to mix the materials evenly. The mixed materials were extruded and granulated by a twin-screw extruder to obtain nucleating agent modified polypropylene pellets. The twin-screw extrusion temperature was 170-210°C, the main engine speed was 200r / min, and the power was 6.0Hz. The prepared pellets were dried in an oven at 80°C for 6 hours to remove moisture, and the injection machine was used to prepare the sample strips. The prepared sample strips were placed in a constant temperature and humidity chamber for 48 hours. The injection temperature of the injection machine was controlled at 200-225°C, the injection time was 20s, the injection pressure was 40MPa, and the holding pressure was 30MPa.
[0039] Table 1:
[0040]
[0041] in:
[0042] Mechanical properties test: The bending performance is tested according to GB / T 9341-2000, the sample size is 80mm×10mm×4mm, and the bending rate is 2mm / min; the tensile performance is tested according to GB / T 1040.1-2018, the sample size is 1A type specimen, and the tensile rate is 50mm / min; the notched impact strength is tested according to ASTM D256-2010E1.
[0043] MFR test: Tested according to GB / T 3682.1-2018.
[0044] Yellowness index test: Tested according to GB / T 39827.2-2021.
[0045] DSC test: N2 atmosphere, first heat up to 200℃, cool down to room temperature, and then heat up again to 200℃. The first temperature increase is to eliminate the thermal history. The temperature change rate is 10℃ / min. Test according to GB / T19466.3-2004.
[0046] The change of nucleating agent type and addition amount has little effect on the MFR of polypropylene, which basically remains at 1.8g / 10min. The nucleating agent affects the crystal morphology of polypropylene and has no effect on the fluidity of polypropylene melt.
[0047] β-nucleating agent TMB-5 has a good improvement on the impact properties of polypropylene. When the addition amount of nucleating agent TMB-5 is 0.1%, the impact strength reaches the maximum, which is 20.7kJ / m2. The impact strength of polypropylene modified by α-nucleating agent is lower than that of unmodified polypropylene. When 0.2% CH-6N is added, the impact strength is only 2.7kJ / m2. For polypropylene modified by α / β-nucleating agent compound, the impact properties are improved compared with unmodified polypropylene. The compound modification effect of 0.1% TMB-5 and 0.1% CH-6N is better, and the impact property is 5.5kJ / m2. β-nucleating agent can effectively improve the toughness of polypropylene. β-nucleating agent induces polypropylene to form β-crystal, which is a thermodynamically metastable crystal form of polypropylene. The unique lamellar arrangement structure of β-crystal can effectively buffer the deformation caused by stress, thereby showing better toughness. α nucleating agent increases the heterogeneous crystal nuclei of polypropylene, increases the number of crystals, reduces the crystal size, and makes the polypropylene structure more regular. When subjected to impact stress, the normalized chain structure cannot buffer the shear stress in time, resulting in a decrease in the impact strength of polypropylene modified by α nucleating agent. For polypropylene modified by α / β nucleating agent compound, the interaction between α crystal and β crystal can achieve a good balance of rigidity and toughness, increasing its rigidity without reducing its toughness.
[0048] α nucleating agents can effectively improve the tensile strength of polypropylene. 0.2% nucleating agent CH-6N has the best reinforcing effect, with a tensile strength of 43.2MPa. The tensile strength of polypropylene modified by β nucleating agent TMB-5 is reduced, mainly because the β nucleating agent plays a toughening purpose, resulting in a decrease in tensile strength. After modification by β nucleating agent, the toughness of polypropylene is greatly improved. 0.1% TMB-5 modified polypropylene has the best toughening effect, with an elongation at break of 530%. α / β nucleating agent compound modified polypropylene can effectively achieve a balance between rigidity and toughness, while increasing tensile strength and maintaining a high elongation at break. 0.1% TMB-5 and 0.1% CH-6N compound modified effect is the best, with a tensile strength of 41.1MPa and an elongation at break of 490%. α nucleating agents can effectively improve the tensile strength of polypropylene. 0.2% nucleating agent CH-6N has the best reinforcing effect, with a tensile strength of 43.2MPa. The tensile strength of polypropylene modified with β-nucleating agent TMB-5 is reduced, mainly because the β-nucleating agent plays a toughening role, resulting in a decrease in tensile strength. After modification with β-nucleating agent, the toughness of polypropylene is greatly improved. The toughening effect of polypropylene modified with 0.1% TMB-5 is the best, and the elongation at break is 530%. The α / β-nucleating agent compound modified polypropylene can effectively achieve a balance between rigidity and toughness, while increasing the tensile strength and maintaining a high elongation at break. The compound modification effect of 0.1% TMB-5 and 0.1% CH-6N is the best, with a tensile strength of 41.1MPa and an elongation at break of 490%.
[0049] The bending modulus of pure polypropylene sample is 1800MPa. Adding α nucleating agent can effectively improve the rigidity of polypropylene. The polypropylene modified with 0.2% CH-6N has the best rigidity enhancement effect, with a bending modulus of up to 2390MPa and a bending strength of 60.6MPa. The rigidity of polypropylene modified by β nucleating agent is poor, and its modulus is lower than that of unmodified polypropylene. α / β nucleating agent composite modified polypropylene has a good balance of rigidity and toughness, while ensuring improved toughness, the rigidity is not reduced. The composite modification effect of TMB-5 / CH-6N is better than that of TMB-5 / HPN-715, and the modulus of PP / TMB-5 / CH-6N reaches 2 140MPa.
[0050] The nucleating agent CH-6N has the best effect on improving the yellow index of polypropylene. The yellow index of unmodified polypropylene is 4.3, and the yellow index of the modified material with 0.1% nucleating agent CH-6N is only 0.46, which is the lowest yellow index. The nucleating agent forms a crystal nucleation center, which increases the density of the crystal nucleus, thereby refining the spherulites. There is a good lattice matching relationship between the nucleating agent crystals and the polypropylene crystals, which greatly reduces the nucleation free energy barrier, resulting in a reduction in the difference in refractive index between the polypropylene macromolecular crystalline phase region and the amorphous phase region, improving its optical properties. After adding the nucleating agent, the melting temperature of polypropylene increases. After adding the β-type nucleating agent TMB-5, there are two endothermic peaks in the melting curve, which are divided into
[0051] The melting peaks of the β-crystal form are near 155°C and 170°C respectively. The melting peak of the β-crystal form is near 155°C, and the melting peak of the α-crystal form is near 170°C. The melting peak of the β-crystal form is greater than that of the α-crystal form, indicating that the β-nucleating agent induces polypropylene to produce a large amount of β-crystal form. The crystallization temperature of pure polypropylene is around 118°C. After adding the nucleating agent, the crystallization temperature of the modified polypropylene is increased to around 130°C, the crystallization temperature is significantly increased, and the crystallinity is increased, indicating that the nucleating agent increases the heterogeneous crystal nuclei, increases the crystallinity of polypropylene, and improves the crystallization performance.
[0052] From the above experiments, we can conclude:
[0053] Mechanical properties:
[0054] α-type nucleating agent has a certain improvement effect on the rigidity of polypropylene. The nucleating agent CH-6N has the best rigidity modification effect on polypropylene, which can effectively improve the mechanical strength of polypropylene, but the α-type nucleating agent causes a slight decrease in the toughness of polypropylene. The β-type nucleating agent TMB-5 can effectively improve the toughness of polypropylene, but there will be a certain loss in rigidity. The appropriate ratio of α / β nucleating agent composite modification can ensure that the toughness is improved without reducing the rigidity, so that polypropylene can obtain a good rigidity-toughness balance effect.
[0055] Optical properties: adding nucleating agent increases the number of crystal nuclei, forms crystal nucleation centers, refines the crystals, forms a good lattice matching relationship between the nucleating agent crystals and the polypropylene crystals, reduces the nucleation free energy barrier, reduces the refractive index difference, and improves its optical properties.
[0056] In terms of thermodynamic properties: nucleating agents can effectively increase the crystallization temperature and crystallinity of polypropylene by increasing the number of crystal nuclei through heterogeneous nucleation. The increase in crystallization temperature allows polypropylene to be processed and formed at a higher temperature, thereby improving the thermal processing properties of polypropylene resin.
[0057] It should be noted that, according to the needs of implementation, the various components described in the embodiments of the present invention can be split into more components, and two or more components or parts of components can be combined into new components to achieve the purpose of the embodiments of the present invention. The above embodiments only express several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent of the present invention. It should be noted that for ordinary technicians in this field, without departing from the concept of the present invention, several variations and improvements can be made, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A special composite additive for low-ash capacitor film polypropylene, characterized by: The proportions of the components are as follows: F401 99.4-99.6% Compound antioxidant 0.4% Nucleating agent 0-0.2%. The compound antioxidant is formulated with a high-phosphorus-content phosphite antioxidant SONOX626 and an inorganic acid absorbent hydrotalcite.
2. The low-ash capacitor film polypropylene special composite additive according to claim 1, characterized in that: The composition ratio of F401 is 99.4-99.5%, and the type of nucleating agent is TMB-5, and the composition ratio is 0.1-0.2%.
3. The low-ash capacitor film polypropylene special composite additive according to claim 1, characterized in that: The component distribution ratio of F401 is 99.4-99.5%, and the type of nucleating agent is CH-6N, and the component distribution ratio is 0.1-0.2%.
4. The low-ash capacitor film polypropylene special composite additive according to claim 1, characterized in that: The component distribution ratio of F401 is 99.4%, and the type of nucleating agent is HPN-715, and the component distribution ratio is 0.1-0.2%.
5. The low-ash capacitor film polypropylene special composite additive according to claim 1, characterized in that: The composition ratio of F401 is 99.4-99.5%, and the type of nucleating agent is TMP-7, and the composition ratio is 0.1-0.2%.
6. The low-ash capacitor film polypropylene special composite additive according to claim 1, characterized in that: The component ratio of F401 is 99.4%, and the type of nucleating agent is TMP-5+CH-6N, wherein the component ratio of TMP-5 and CH-6 is 0.1% each.
7. The low-ash capacitor film polypropylene special composite additive according to claim 3, characterized in that: The component distribution ratio of F401 is 99.4%, and the type of nucleating agent is TMP-5+HPN-715, wherein the component distribution ratio of TMP-5 and HPN-715 is 0.1% respectively.